The treatment of trigeminal neuralgia by posterior fossa microsurgery. Issue 11 (November 1982) - Adams, C B; Kaye, A H; Teddy, P J
Abstract : Between 1972 and 1981 57 patients underwent posterior fossa exploration in Oxford by a single surgeon for the treatment of trigeminal neuralgia. Fifty-four of these had either partial or total section of the trigeminal sensory root, 2 had microvascular decompression operations and one had both a partial sensory root section and microvascular decompression. There was no mortality and no significant morbidity. Fifty-four patients were followed up for a mean period of 4 . 5 years. Fifty-two patients (96%) had either no further pain or only minor twinges requiring no further treatment. Two other patients who had partial sections suffered no further trigeminal neuralgia after subsequent total sections. One patient who had a partial root section developed anaesthesia dolorosa and one who had a microvascular decompression developed painful dysaesthesia. All patients having partial root sections retained previously intact corneal responses–the sensory impairment in the face corresponded to the appropriate part of the portio major cut. Only 11% of patients were found to have a vascular abnormality.